Evaluating Banks’ Performance That Operating in Iraq according to the International Indicators System (CAMELS); An applied study on Trade Bank of Iraq (TBI) for the period 2014-2017 - RASHID, AHMED MUSHRIF; SALEH, AHMED FADHIL; JASIM, SINAN RAHEEM; HAMIN, ASSAD FARHAN (International Journal of Psychosocial Rehabilitation, 2020)
The research shows banking evaluation system by using CAMELS’s indicators. The study included Trade Bank of Iraq (TBI) to identify banking risks that constitute weaknesses in the financial and administrative operations of the bank. A descriptive approach has been utilized in collection and analysis of published financial statements of Trade Bank of Iraq (TBI) depending on CAMELS’s system for four financial years started from 2014 to 2017. The research results indicate that Trade Bank of Iraq (TBI) has got a strong classification according to the policy of composite evaluation of (CAMELS). The results also indicate the bank was in the right path regarding to the growth of its strongly performance, its assets, the management, and determination of appropriate levels of capital & profits reasonable distribution. The study showed the importance of U.S. banking evaluation system (CAMELS), through which the positive aspects of its application and its role in feedback and information control to reveal some of weaknesses and deficiencies in early way. CAMELS also helped the Trade Bank of Iraq (TBI) to perform a comprehensive analysis of the Bank’s performance and comparison to the industry level in the banking environment which helps management by focusing on their financial positions. As well as, it encourages the Central Bank of Iraq (CBI) in terms of monitoring other banks operating in Iraq and follow-up global developments related to specialized systems of financial analysis and control and various types of banks